Pride and the suffering of the poor in the Persian period : Psalm 12 in its post-exilic context - Botha, Phil J. (Old Testament essays, 2012)
This paper contends that Ps 12 should be read, as part of the composition Pss 9-14, as a response to and an explication of Prov 30:1-14 by exponents of Wisdom thinking in the Persian period. The suffering of the righteous people in Ps 12 is described as the result of arrogant Jewish and also non-Jewish rulers who use speech as an instrument of deception, fraud, flattery, boasting, and questioning Yahweh's authority in order to oppress and intimidate believers. It is proposed that the historic context of the final form of the text was that of the "piety of the poor," atheology which developed from the need to restore dignity and provide hope to victims of social and religious oppression in the post-exilic era. It would seem that these people sought comfortin the word of Yahweh and that they found vindication for themselves in those sections of the developing "canon" which promised that Yahweh would intervene on behalf of those people who represented true humility and piety.